The Czech Republic Between Studentocracy, Academic Oligarchy and Managerialism: Are students powerful or powerless? - Pabian Petr; Hündlová Lucie; Provázková Karla (Routledge, 2011)
In this article, we will argue that students played an important role at several crucial junctures of modern Czech history, which secured them a central position after 1989 in the new democratic model of higher education governance. However, over the last two decades students have largely lost this position owing to several factors: the growing indifference among the expanding student population, the ascendancy of academics’ power and the proliferation of managerial approaches to higher education governance. We thus conclude that the golden age of Czech academic democracy with a strong student presence is over and that student roles will have to be redefined within the framework of academic oligarchy and/or managerialism.
ČR mezi studentokracií, akademickou oligarchií a manažerialismem: jsou studující mocní nebo bezmocní?
Keywords: governance; student experience; widening access/participation; vládnutí; studující; vysokoškolská politika